Design of Solar Powered Charging Backpack - Jonas Taverne; Firdaus Muhammad-Sukki; Ahmad Syahir Ayub; Nazmi Sellami; Siti Hawa Abu-Bakar; Nurul Aini Bani; Abdullahi Abubakar Mas’ud; Draco Iyi (Institute of Advanced Engineering and Science, 2018)
This paper demonstrated a step by step process in designing a solar powered charging backpack that is capable of charging a mobile phone efficiently. A selection of existing products available on the market were reviewed and compared to ascertain the cost, size, and output capabilities. Next, the solar cell types and regulators were compared and their respective merits were also investigated. The charging system was then designed and tested before being integrated with the backpack. The results clearly showed that the system managed to charge the mobile phone. However, it was found that the excessive power dissipation has caused the linear regulator to generate significant heat.